Análise da operação de motores diesel com misturas parciais de biodiesel - Bueno, André Valente (2006)
The consequences of the biodiesel blends with diesel fuel were analyzed establishing cause and effect relationships between the engine performance and the combustion and mixture preparation processes. In this investigation, aspects like pollutant emissions, mixture preparation, dynamic of the combustion process, fuel conversion efficiency, performance under full load and specific fuel consumption were included. Techniques traditionally associated with diesel engines research and development were utilized for this purpose, including heat release analysis, exergetic analysis and dynamometric bench tests. In order to account for the small effects of the biodiesel introduction on the engine operational parameters, some modifications of the methods and models applied to data acquisition and post-processment were necessary. These modifications include the formulation of a new model for the in cylinder exergetic analysis and a novel arrangement of indicator system. By using the exergetic analysis, it was demonstrated that the blending of biodiesel in low concentrations increases the conversion of fuel exergy into work within the cylinder, causing an elevation on the engine efficiency. For the analyzed fuels, which enclose up to 20% of biodiesel addition in volume, the 10% biodiesel blend has presented the best results of performance and specific fuel consumption.